2021
DOI: 10.1007/s10815-021-02199-w
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial nicotinamide adenine dinucleotide hydride dehydrogenase (NADH) subunit 4 (MTND4) polymorphisms and their association with male infertility

Abstract: Purpose The purpose of the present study was to determine the relationship between infertility and the polymorphisms of mitochondrial NADH dehydrogenase subunit 4 (MTND4) by spermatozoa analysis in fertile and subfertile men. Methods Samples were divided into 68 subfertile men (case group) and 44 fertile men (control group). After semen analysis, samples were purified. The whole genome was extracted using a QIAamp DNA Mini Kit and the mitochondrial DNA was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Besides, two studies were conducted in our laboratory, the first study demonstrated that the frequencies of total mitochondrial variants in four mitochondrial genes (nicotinamide adenine dinucleotide hydrogen (NADH) dehydrogenase 1 (ND1), NADH dehydrogenase 2 (ND2), NADH dehydrogenase 5 (ND5), and NADH dehydrogenase 6 (ND6)) were negatively correlated with the percentages of sperm motility and ICSI outcomes, namely 13708 G>A, 4216T>C and 12506T>A [ 5 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, two studies were conducted in our laboratory, the first study demonstrated that the frequencies of total mitochondrial variants in four mitochondrial genes (nicotinamide adenine dinucleotide hydrogen (NADH) dehydrogenase 1 (ND1), NADH dehydrogenase 2 (ND2), NADH dehydrogenase 5 (ND5), and NADH dehydrogenase 6 (ND6)) were negatively correlated with the percentages of sperm motility and ICSI outcomes, namely 13708 G>A, 4216T>C and 12506T>A [ 5 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, G11719A (rs2853495) and A11251G (rs869096886) in gene MTND4 were also tied to male infertility. Therefore, even if the genotype of the allele is different, the presence of the allele itself could still be tied to male infertility [ 109 ].…”
Section: Mitochondrial Genome Mutations/variations and Male Infertilitymentioning
confidence: 99%
“…Previous studies have demonstrated a strong association between impaired mtDNA and the development of male infertility conditions such as asthenozoospermia, oligozoospermia and teratozoospermia (Dahadhah et al, 2021). For instance, large-scale deletions in the mtDNA were reported in asthenozoospermia in different populations (Al Zoubi et al, 2020;Bahrehmand Namaghi & Vaziri, 2017;Kao et al, 1998).…”
Section: Introductionmentioning
confidence: 99%